Shades of Pink. Reykjavík a gay-friendly destination - Verdugo, Julio César León, 1986- (2015)
The purpose of this paper is to learn from gay men’s previous travel experiences and what destination they have experienced as more gay-friendly. This research first reviews the concept of destination image, and what influences in creating the image of a destination, to later apply this concept to understand what factors play a role in the image creation of a gay destination. The push and pull factors theory is also analyzed to explore the elements that influence gay men to visit a new destination. This research specially focused on finding out how gay welcoming and gay-friendly is the most northern capital of Europe, Reykjavík. For the purpose of this research gay men were interviewed about their travel experiences, the interviews were formulated to explore four themes, which are destination image, gay push and pull factors, Reykjavík as a destination and Reykjavík as a gay-friendly destination. In-depth interviews were used to gain a richer data. All individuals who took part in this study had visited Reykjavík. Through the interviews, Reykjavík seemed to be in gay men’s mind as a really welcoming LGBT destination, and Reykjavík seemed to be a desirable destination for gay men although it wasn’t necessary in their top five or next place to visit, but it was rather external factors that made them visit. LGBT events were one of the main reasons why they decided to visit Reykjavík. As most of LGBT studies this research only focused on one of the individual groups of the LGBT community, gay men, which mean lesbians, bisexuals and transgender are excluded from this study. This study analyses gay men’s travel experience and emphasis in their visit to Reykjavík to find out how gay-friendly Reykjavík is.